ENVIRONMENTAL LITERACY ASPECT CONTENT IN BIOLOGY TEXTBOOK FOR 10th-GRADE SENIOR HIGH SCHOOL - Pipit Marianingsih; Annisa Firdausy; Adi Nestiadi; Suroso Mukti Leksono (Universitas Sultan Ageng Tirtayasa, 2021)
Environmental problems have become a global issue. Understanding and interpreting environmental conditions to take appropriate actions to improve and to maintain the quality of the environment is known as environmental literacy. Environmental literacy values are essential to be included in textbooks since they can increase environmental awareness. This study aims to identify and analyze the content of environmental literacy aspects in biology textbooks for 10th-grade senior high school. This research was descriptive qualitative research with investigator triangulation technique for data validation. This research was conducted from December 2020 to June 2021. Based on the results showed that six aspects of environmental literacy were included in nine chapters (of the ten chapters) in the 10th-grade biology textbook, with the highest score of 36% (knowledge issues and environmental problems aspect) and the lowest score of 6% (cognitive skills aspect). Further, based on the results of expert validation, it got an average value of 98%, in the very appropriate category. The research results can be used as a reference for developing learning tools that are oriented towards increasing students' environmental awareness.